The power of speech: the socio-political unconscious - Ramos Bermúdez, Marco Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
To understand and comprehend the emergence of a new discourse in Bolivia between 2005 and 2015, it will be necessary to study the triggering sociopolitical symptoms from 2000 to 2004, but to understand these decades in depth and globally, it is necessary to go to the past, review two centuries more or less of history, repression and repressed contents, to then analyze and later make a diagnosis of the Bolivian reality, in this way we will be able to recognize the intimate philosophical and political aspects of this reality, establishing some essential guidelines of neo-ontology.